Study on the Dynamics Characteristic of Gear Cutting Tooth Fault Under Variable Load Excitation - Shi Peiming; Zhao Na; Dang Hui; Tian Guangjun (Jixie chuandong)
In order to grasp the dynamics characteristic of gear cutting fault under variable load excitation,considering the quality imbalance of gear caused by the cutting tooth fault and the influence of the fault on meshing stiffness of gear system,the dynamics model of the 4 freedom degree gear including cutting gear fault is established. On the basis of that,the variable step size four- order Runge- Kutta numerical method is used to solve to the dynamics model and the dynamics mechanism of gear cutting tooth is studied. Comparison of the dynamics characteristic of gear cutting tooth with non- load and variable load excitation,the dynamics characteristic of gear cutting tooth are analyzed. The result shows that,with variable load excitation,gear cutting tooth system has obvious low frequency components,and the more intense the external load changes,the low- frequency component is more obvious; the vibration displacement of the gear is similar to the external load. The size of the variable load also has effect on the dynamics characteristic of gear cutting tooth. The larger of variable load,the impact phenomenon and modulation phenomenon of the time- domain diagram is not more obvious and side band spectrum is no longer a cutting tooth gear rotating frequency. Therefore,for the gear fault diagnosis,the fault diagnosis should be carried out with the condition of stable and small load.